METHOD OF DETECTING CENTRAL SIGNS OF EMERGENCY SITUATION DUE TO FIRE AT CRITICAL INFRASTRUCTURE FACILITIES - Shcherbak, О.; Derevyanko, О.; Neshpor, О.; Shevchenko, R. (Municipal economy of cities (Technical science), 2023)
The work is devoted to the solution of an actual scientific task in the field of civil protection, namely, the development of a method for detecting focal signs of an emergency situation due to a fire at critical infrastructure facilities, with the aim of further developing a method of preventing terrorist emergencies at critical infrastructure facilities of Ukraine. In order to solve the set goal, it is necessary to: provide a description and carry out planning of the procedure for conducting a full-scale experiment to determine the focal signs of an emergency situation due to a fire at critical infrastructure facilities; determine requirements for equipment for measuring focal signs of an emergency situation due to fire at critical infrastructure facilities; determine the general conditions for the formation of an algorithm for the method of detecting focal signs of an emergency situation due to a fire at critical infrastructure facilities; provide recommendations on the possible use of the received information during the reconstruction of an emergency situation due to a fire at a critical infrastructure facility. This work is a continuation of the cycle of previous works on the development of structural, logical and mathematical models for managing an emergency situation of a terrorist nature at an object of the critical infrastructure of Ukraine, which is protected, which are intended for the development and constant implementation of procedures of an organizational and technical nature that ensure the safety of the object. Thus, the interpretation of the results of the measurement of electrical resistance must be accompanied by an analysis of the specifics of the volume-planning decisions of the building (premises), the conditions of air exchange, the distribution of the fire load in the center of an emergency situation due to a fire. The obtained results of the soot research can be used as part of the technical examination to reconstruct the process of the emergence and development of an emergency situation due to a fire at critical infrastructure facilities.